Exploring the Impact of Climate Change on Food Production in Oyo Township, Oyo State - Ayanwale, O.; Fawole, O. A. (Emmanuel Alayande University of Education Journal of Multidisciplinary Studies (EAUED-JMS), 2025)
The study examined the impact of climate change on food production in Oyo township, Oyo State. The study assessed the viewpoints of respondents across age group and educational background. The sample selected for the study was 150 respondents drawn from Oyo West, Oyo East and Atiba Local Government Areas of Oyo State respectively. The study employed simple random sampling and purposive sampling techniques to select the sample. A 30 items questionnaire bothering on the Impact of Climate Change (ICC) was used for the study. The study stated three research questions. The data analysis tools were Descriptive and Inferential statistics, use of table and ANOVA. The validation of Impact of Climate Change Test (ICCT) was carried out to authenticate its reliability. The instrument was administered to the people in Afijio Local Government which is outside the study areas. The results of this trial study were subjected to further validation using KR-20 and Cronbach Alpha which yielded an alpha value of 0.76 and average item difficulty index of 0.4-0.6. Findings revealed that the three major food items that were very high in price are beans, tomatoes and pepper and cassava products. The least food items that were a little bit less in price are sweet potato, onion and fruits. Differences existed in the perception of different age groups on the seriousness of climate change on beans, tomatoes and pepper and cassava products. The paper recommends among others that whoever farmers that want to embark on farming activities should prepare themselves ahead to look for river basin area so that they can do a little of watering their farm products during the period of shortage of rainfall. Also government at all levels should be of help to farmers through the irrigation method.